The Effect of Tone Changes on The Interjection of ‘Aiya’ (哎呀) in Attitude and Emotional Signals - Fikry Prastya Syahputra; Feby Yoana Siregar (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
The purpose of this research is to prove that modification of the interjection ‘Aiya’ [哎呀] at certain intonation signals a different attitude. As a result, this study focuses on the different emotional expressions that the Chinese word aiya might convey. Re-searchers employed recording methods with the PRAAT application. Furthermore, the researcher presented 40 respondents who were Mandarin students to give a direct as-sessment of the original and the manipulated interjection. The perception test is carried out by playing five interjection utterances without telling the respondent which sound is the initial utterance. The first sentence has the results of happy emotional attitudes. When it is raised and lowered to 4 semitones, there is a balanced variation of emotions. However, when it was raised to 8 semitones, the test results show an emotional attitude of disappointment, and when lowered to 8 semitones, showed an emotional attitude of impressed. An increase of one tone point can create a positive impression. Then, if there is a decrease, it will make a negative impression. However, because of the vast variation in everyone's perception, generating these conclusions is still impossible. This is where the suggestion appears for future researchers to continue this research and make this research a reference.